Women's roles in decision-making and nutrition-sensitive agriculture - Feiruz Yimer Mohammed; Makaiko G. Khonje; Matin Qaim (Food Security, 2025)
The small-farm sector is home to many of the world's food-insecure and undernourished people. Strategies to make smallholder farming more nutrition-sensitive often focus on agricultural diversification. In addition, women's empowerment is widely considered useful to improve diets and nutrition. Many studies have analyzed the effects of farm production diversification and of women's empowerment on dietary outcomes, but mostly in separate strands of literature. Here, we connect these strands to contribute to a better understanding of the multifaceted links between farm production diversity, women's roles in decision-making, and household diets. Using primary data from Malawi, we show that women's decision-making is positively associated with farm production diversity and with household dietary diversity. Furthermore, women's decision-making increases the positive association between farm production diversity and dietary diversity. We also differentiate between different domains of decision-making, including agricultural production, market sales, cash income control, and food purchases. The results suggest that strengthening women's agency can make smallholder farming more nutrition-sensitive through multiple channels.
Keywords: 630; Farm production diversity; Dietary diversity; Female decision-making; Nutrition; Africa; Malawi